Description of Birth Distance Related to the Risk of Stunting in Children At Dharma Women's Kindergarten Dukuh II, Ngaduluwih District - Ardina Rezky Noeraini; Entin Srihadi Yanti; Eko Sri Wulaningtyas; Ririn Ita Purnamasari (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Stunting is a condition where a toddler experiences long-term failure to thrive due to malnutrition. The prevalence of stunting according to WHO in 2018, Indonesia is the third country with the highest average prevalence of stunting in the Southeast Asia/South-East Asia Regional (SEAR). The prevalence of stunting in East Java continues to decrease, but this has not reached the target set by the WHO of 20% and is still a major problem that occurs in toddlers. The incidence of stunting can be seen from two sides, namely toddlers and mothers. One of the risk factors from the mother's point of view is birth spacing. The purpose of this study was to get an overview of birth spacing related to the risk of stunting in Dharma Wanita Dukuh II Kindergarten, Ngadiluwih District. This type of research is descriptive and quantitative. The population in this study were all mothers with children under five who were in Kindergarten Dharma Wanita Dukuh II, Ngadiluwih District. The instrument used is a questionnaire. A univariate data analysis was performed to determine the frequency and percentage of research variables. The results of the study showed that the most common birth spacing was in the 2 year category with 24 respondents (68.6%). It is hoped that mothers who have a large number of children with close birth spacing can improve their parenting, not only in terms of nutritional needs but also the psychological needs of the child. The community must also begin to regulate birth spacing, considering this will affect the nutritional status of children, which can lead to stunting. In addition, there is a need to increase counseling related to birth spacing by medical personnel as a form of effort to prevent stunting.